Effect of Locus of Control, Self-Efficacy, and Personality Type on the Quality of Life among Caregivers of Schizophrenia Patient in Godean Sub-District, Yogyakarta - Mulyanti -; Rita Benya Adriani; Setyo Sri Rahardjo (Masters Program in Public Health, 2017)
Background: Caregivers of schizophrenia patients have an important role in fulfiling the need of patients. This task implicates on care burden and physological problems on the caregivers. The quality of life of the caregivers may have important impact on the caring process. This study aimed to examine effect of locus of control, self-efficacy and personality type on the quality of life among caregivers of schizophrenia patient.Subjects and Method: This study was analytic observational with cross-sectional design. It was carried out at Godean Sub-District, Yogyakarta, from March to April 2017. A sample of 102 caregivers of schizophrenia patient were selected for this study by fixed diseases sampling. The dependent variable wa quality of life. The independent variables were age, gender, personality type, locus of control, self-efficacy, family concern, family income. The data was collected by questionnaire, and analyzed by path analysis.Results: Higher quality of life of caregivers was affected by self-efficacy (b=0.46; SE=0.15; p<0.001), extrovert personality (b=0.21; SE=0.10; p=0.01), and higher family income (b=0.18; SE=0.05; p=0.02). Self-efficacy was affected by better family concern (b=0.22, SE=0.16; p=0.02) and extrovert personality (b=0.33; SE=0.06; p<0.001).Conclusion: Higher quality of life of caregivers was directly affected by self-efficacy, extrovert personality, and higher family income. Higher quality of life of caregivers was indirectly affected by better family concern and extrovert personality.Keywords: quality of life, locus of control, self-efficacy, schizophrenia, caregiverCorrespondence: Mulyanti. Masters Program in Public Heath, Sebelas Maret University, Surakarta. Email: kalilaputri2811@gmail.com. Mobile: +6285868823105.Journal of Epidemiology and Public Health (2017), 2(1): 20-31https://doi.org/10.26911/jepublichealth.2017.02.01.03